الخلع الرضائى وأحكامة - المستريحي، محمد أحمد (جامعة أسيوط - مركز تطوير التعليم الجامعي, 2013)
بعد الخلع الرضائي أحد طرق انحلال عقد الزواج ويقع باتفاق الزوجين أمام القضاء مقابل عوض تدفعه الزوجة لزوجها للخلاص منه، وانطلاقا من أهمية هذا الموضوع في الحياة العملية، فقد أولاه الفقه اهتماما كبيرا، لذا اعتمدنا في بحث هذا الموضوع اسلوب الدراسة المقارنة، من حيث طرح آراء فقهاء المسلمين، وأدلتهم، وقد تناولنا هذا الموضوع في ثلاثة مباحث، خصصنا المبحـث الاول: لمفهوم الخلع الرضائي وأدلة مشروعيته وحكمه، وكرسنا المبحث الثاني: في شروط الخلع الرضائي في الفقه والقانون وهل الخلع طلاق ام فسخ وعدة المختلعة رضائيا، وتناولنا في المبحث الثالث: مسائل متعلقة بما يأخذ ماليا في الخلع الرضائي. وأنهينا البحث بخاتمة تضمنت أهم ما توصلنا إليه من نتائج.
Consensual divorce is one of ways the dissolution of marriage contract, the agreement of the couple in court for a valuable consideration paid by the wife to her husband to get rid of him. According to the importance of this topic in practical life, the jurisprudence has placed much attention, so we have adopted in this topic the style of comparative study in terms of put forward the views of Muslim jurists, and their evidence. This topic was dealt in three sections. We allocated the first topic as: the concept of consensual divorce and legitimacy and its evidence. We devoted the second topic: in terms of consensual divorce in jurisprudence and law and whether divorce or annulment. We addressed in the third topic: related issues including takes financially to the consensual divorce. Finished research conclusion included the most important our findings.
Keywords: الفقه الإسلامى -- الخلع الرضائى -- عقود الزواج -- العلاقات الزوجية -- الأحكام الشرعية